The Birmingham Journal, H-Bomb special, 1959 (1959)
1959 1945-1960 "The Birmingham Journal, H-Bomb special, 1959" [T0362.jpg], 1959 This special edition of the 'The Birmingham Journal', published by the Birmingham Trades Council in September 1959 publicises a march organised by the Campaign for Nuclear Disarmament (CND), which had been formed the previous year.